Competencias digitales de Desarrollo de contenidos digitales educativos de los docentes de bachillerato general unificado de la Unidad Educativa Fiscomisional La Dolorosa, sección matutina, en el año lectivo 2021-2022 - Buri Orosco, Elian Andres (2023)
This research focuses on the study of the skills that all pedagogy professionals must possess in their professional work. It also seeks to provide a contribution to the scientific literature on digital teaching skills related to the development of educational digital content considered as the set of skills that allow the teacher to use technology to transform the teaching process and motivate their students to continue learning in an innovative and interactive way. Its objective is to define the competences for the development of educational digital content of the teachers of Unidad Educativa Fiscomisional La Dolorosa, morning section, during 2021-2022 school year, based on what is defined by the Common Framework of Competence Digital Teaching proposed by the National Institute of Educational Technologies and Teacher Training (INTEF), in addition, the research was developed under the quantitative approach with an exploratory-descriptive scope. The population under study was made up of 30 teachers from the different areas of knowledge who teach classes in Bachillerato General Unificado of the analyzed educational institution. For the collection of data and information, a structured-based questionnaire was used, the same one that was applied in a survey form, considering the most relevant results, it is determined that half of the teachers of the educational institution under study are competent to create educational material in different formats, as well as have skills to search, save, edit and share their projects in academic communities through emerging technologies. Keywords: Digital competences, educational digital development, Teaching Digital Competence.